Post-traumatic stress disorder and its associated factors among school-going children exposed to a tsunami disaster in Malaysia - Idris I.B.; Shamsudin K.; Aniza I.; Khairani O.; Rahmah M.A.; Hod R. (Malaysian Public Health Physicians Association, 2024)
Indexed by Scopus